STRATEGI PENINGKATAN PERILAKU ORGANISASI POSITIF DALAM MEWUJUDKAN SEKOLAH YANG BERKUALITAS DI SMPIT BUNAYYA PASAR KEMIS - Sugeng; Ersam Mahendrawan; Sholihin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the principal's strategy in improving positive organizational behavior, analyze supporting and inhibiting factors, contribute to quality schools, and provide strategic recommendations for principals at SMPIT Bunayya. This study uses a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation with the principal as the main informant and teachers and students as triangulation informants. Data analysis was carried out through the stages of open coding, axial coding, and selective coding, then interpreted to obtain research themes. The results showed that the principal's strategy was carried out through the implementation of the 5S culture, collaborative learning, giving trust to students, OSIS and LDK activities, giving appreciation, and strengthening cooperation with parents and the community. Supporting factors include the principal's commitment, teacher involvement, and parental and community support, while inhibiting factors come from the characteristics of generation Z students who still need to strengthen motivation, independence, and fighting spirit. Positive organizational behavior contributes to improving the quality of learning, character building, improving student achievement, and creating a conducive school culture. Based on the research results, it can be concluded that consistently implemented principal strategies can foster positive organizational behavior as a foundation for realizing quality schools. The findings of this study yield recommendations for strengthening organizational culture, increasing collaboration among all school members, developing sustainable character, and implementing coaching as an effort to improve school quality